Atopic dermatitis is an important problem in current pediatrics - S.L. Nyankovskyy; O.S. Nyankovska; M.I. Horodylovska (Zaslavsky O.Yu., 2019)
The article summarizes the data on atopic dermatitis problem in pediatric practice, in particular, the issues of its diagnosis and treatment are considered. Atopic dermatitis is the most common skin disease in children, which greatly reduces small patients quality of life. It is well known that this disease is the result of the complex interaction of defects in the barrier function of skin, immune dysregulation, and environmental and infectious agents. There are no specific diagnostic tests for atopic dermatitis. There is no pathognomonic laboratory biomarker for its diagnosis. One of the earliest and most recognized diagnostic criteria is the Hanifin and Rajka diagnostic criteria of 1980. The diagnosis is performed in the presence of three main criteria and three additional criteria. Approaches to its treatment and choice of effective and safe treatment method in childhood are particularly relevant in recent years. For children with atopic dermatitis, a differentiated, integrated approach to treatment is necessary. Successful treatment requires a multifaceted approach that involves teaching of the patient and care-takers, elimination diet in the event of a food allergy, optimal skin care, anti-inflammatory therapy with topical corticosteroids and/or topical calcineurin inhibitors, and treatment of skin infections. The main part of treatment is daily proper skin care. The use of moisturizers enhances the hydration of the skin. Emollients can reduce the inflammation and the severity of the disease. In addition, their use reduces the amount of anti-infectious agents to fight the disease.